a HUBUNGAN MODEL PEMBELAJARAN TUNTAS DAN PENGGUNAAN METODE DISCOVERY TERHADAP KARAKTER SISWA SMA KRISTEN CITRA BANGSA KUPANG - Benu, Asti Yunita (Lembaga Penelitian dan Pengabdian Universitas Nahdlatul Ulama Blitar, 2019)
Educations considered as a means to shape character, particularly through a form of learning proscess. In a learning process which is still dominated by a teacher centered approach, it is further argued that unappropriate methods are being applied by teachers. Teachers sametimes treat students as objects and not as subjects. This research aims to: (1) identify relationship between complete learning model and students character on SMA Kristen Citra Bangsa Kupang, (2) identify relationship between discovery model and students character on SMA Kristen Citra Bangsa Kupang, and (3) identify relationship of complete learning model and discovery model towards students character on SMA Kristen Citra Bangsa Kupang. This research is a quantitative study through a correlation analysis in which data was collected through questionnaire spread to objects of usearch. This research undergoes a series of tests of validity, reliability, normality, homogeneity and a t-test. Test results point correlation between X1 towards Y with a tcount of 2.819, and ttable with a .05 significance level as 1.721. Correlation between X1 dan X2 towards Y points an R of .67, F of 12.77, and p of .000 > .005. Based on these results, conclusion is drawed as: (1) there is positive and significant relationship between complete learning model an students character, (2) there is a positive and significant relationship between discovery model and students character, and (3) there is a positive and significant relationship between complete learning and discovery model towards students character.